Residue Distribution and Depletion of Ractopamine in Goat Tissues After Exposure to Growth-Promoting Dose. Issue 2 (22nd November 2018) - Zhao, Zhen; Gu, Xu; Li, Junguo; Li, Jun; Xue, Moyong; Yang, Xiaowei; Gao, Yunfeng; Qin, Yuchang
Abstract: The objectives of the present study was to investigated the ractopamine (RAC) distribution and depletion process in various tissues of goat including liver, kidney, spleen, lung, heart, fat, bile, brain and the eyes. The experiment was carried out on 21 goats (18 treated and 3 controls). Treated goats were orally administered RAC in a dose of 1 mg/kg body mass per day for last 28 days and randomly sacrificed on withdrawal days of 0.25, 1, 3, 7, 14 and 21. RAC in all matrices were determined by ultra-high performance liquid chromatography–quadrupole orbitrap high resolution mass spectrometry. After 21 days treatment discontinuation, the levels of RAC in bile reached at 13.48 ± 3.36 mg/L, which was significantly higher than that in the other tissues. The concentrations of RAC were followed by kidney, the excretory organ and liver, the major metabolic organ (4.49 ± 0.16 mg/kg for kidney and 1.81 ± 0.11 mg/kg for liver, respectively). The residual concentration of the drug in the eyes of goat was less than that in bile, kidney, liver, lung and spleen on withdrawal days 0.25. RAC residues was higher than the limits of detection = 0.15 μg/mL in liver on Day 21. These findings demonstrated that liver can serve as an alimentary matrix and as a matrix for the control of RAC abuse hypothetically except for urine.